ANALISIS SISTEM DAN PROSEDUR PENERIMAAN KAS PENDAPATAN ASLI DAERAH (PAD) PADA BADAN PENGELOLA PAJAK DAN RETRIBUSI DAERAH KOTA MANADO - Polii, Juanda Jeniver; Elim, Inggriani; Pusung, Rudy (Universitas Sam Ratulangi, 2018)
Reform is a step taken by the government, one of which is in the area of local government financial management funds. Demands for the creation of good governance that has become the will of most people in achieving the goals and ideals of the nation and state. Accountability philosophically arises because of the power in the form of mandates / mandates given to someone to carry out their duties in order to achieve a certain goal by using existing supporting facilities. This study aims to analyze whether the system and procedures for implementing PAD receipts in the Regional Tax and Retribution Management Board of Manado City are adequate. The method of analysis used in this study is descriptive method. The results of this study indicate that the system and procedures for cash receipts carried out by the Regional Tax and Retribution Management Board of the City of Manado are in accordance with the systems and procedures contained in PERMENDAGRI 59 of 2007 for cash receipts, especially in regional taxes and leviesKeywords : Systems and Procedures, Cash Receipts, Local Revenue, Tax Management and Retribution Board of the City of Manado, PAD.